How students with autism spectrum conditions understand traditional bullying and cyberbullying. Issue 4 (3rd April 2018) - Hwang, Yoon-Suk; Dillon-Wallace, Julie; Campbell, Marilyn; Ashburner, Jill; Saggers, Beth; Carrington, Suzanne; Hand, Kirstine
ABSTRACT: Students with ASC are at heightened risk for bullying and their understanding of bullying is known to protect them from involvement in it (Humphrey and Hebron 2015). However, only a handful of studies have examined how students with ASC understand traditional bullying and none of them focused on cyberbullying. To fill this gap, we investigated how traditional bullying and cyberbullying are understood from the perspectives of 89 students with ASC attending inclusive schools and 490 students without ASC. Twenty vignettes were used from (Campbell et al. 2017a), based on the Olweus (1999) definition of bullying and verified by a Delphi technique. In the majority of traditional bullying and cyberbullying vignettes, students with ASC made more accurate responses than inaccurate ones and demonstrated higher accuracy rates than students without ASC. Findings of linear multiple regression analyses pointed out ASC status as a predictive variable for understanding both types of bullying, along with students' age for understanding cyberbullying. The findings highlight the ability rather than inability to understand bullying in students with ASC. It is therefore critical to include the voices and experiences of students with ASC in our research endeavour.